2014
DOI: 10.1002/jcu.22177
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of intracardiac echocardiography with a mechanical probe for catheter‐based interventions: A 10‐year prospective registry

Abstract: Mechanical ICE may offer a valid alternative to conventional TEE in guiding congenital heart disease interventional procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…1,5,7,9 Intracardiac echocardiography-sizing Intracardiac ultrasound provides high-resolution images and can clarify the IAS anatomy better than TEE. 11 It has been shown that ICE sizing of the ASD is precise and accurate 6,9,16 ; in our study, the ICE intraprocedural measurement of the ASD often allowed the correction of the TEE preliminary measurement. These data emerged above all in small defects (with a diameter of less than 10 mm), where the sizing balloon was not performed and the measurement of the two orthogonal diameters of the defect with ICE was decisive for the choice of the device.…”
Section: Intracardiac Echocardiography Monitoring For Less Experience...mentioning
confidence: 56%
“…1,5,7,9 Intracardiac echocardiography-sizing Intracardiac ultrasound provides high-resolution images and can clarify the IAS anatomy better than TEE. 11 It has been shown that ICE sizing of the ASD is precise and accurate 6,9,16 ; in our study, the ICE intraprocedural measurement of the ASD often allowed the correction of the TEE preliminary measurement. These data emerged above all in small defects (with a diameter of less than 10 mm), where the sizing balloon was not performed and the measurement of the two orthogonal diameters of the defect with ICE was decisive for the choice of the device.…”
Section: Intracardiac Echocardiography Monitoring For Less Experience...mentioning
confidence: 56%
“…16 Intracardiac echocardiography (ICE) has been showed to be more precise then TEE in the study of the right atrium anatomy and interatrial septum: EV/CN can be detected with better accuracy by ICE than by TEE. 17 From what we discussed above, it sounds likely that iCTD, although it cannot be defined as true CTD, can be considered as an extreme prominence of the venous valve, possibly associated with both pathophysiological and technical implications. ICE helped to assess accurately the presence of venous valves and in particular of iCTD in patients undergoing interatrial shunt closure procedure, both anticipating potential challenge during the interventional procedure itself and elucidating the pathophysiology of both PFO and ASD.…”
Section: Discussionmentioning
confidence: 97%
“…As previously reported by TEE studies an EV is present in 48% of patients with cryptogenic stroke and a large CN is associated with PFO in 83% of cases . Intracardiac echocardiography (ICE) has been showed to be more precise then TEE in the study of the right atrium anatomy and interatrial septum: EV/CN can be detected with better accuracy by ICE than by TEE …”
Section: Discussionmentioning
confidence: 99%
“…Although a number of recent studies in literature reported the long‐term faith of patent foramen ovale (PFO) closure, follow‐up data are currently limited to relatively small sample of patients over a maximum of 10 years with no clear mention to the imaging tool used to guide the procedure and with poor characterization of long‐term complications. Intracardiac echocardiography (ICE) has been suggested to improve interatrial shunt device closure outcomes . Currently, there are no studies assessing the very long‐term outcomes of ICE‐aided PFO device closure.…”
Section: Introductionmentioning
confidence: 99%
“…Intracardiac echocardiography (ICE) has been suggested to improve interatrial shunt device closure outcomes. [5][6][7] Currently, there are no studies assessing the very longterm outcomes of ICE-aided PFO device closure. Our study is aimed to evaluate the long-term outcomes of ICE-aided PFO device closure in terms of incidence of atrial fibrillation (AF), aortic or free atrial wall erosion, device thrombosis (DT), new onset or worsening of significant mitral valve regurgitation (MVR), and recurrent cerebral paradoxical embolism.…”
Section: Introductionmentioning
confidence: 99%